Pregnancy complications and risk of preterm birth according to maternal age: A population‐based study of delivery hospitalizations in Alberta. (26th December 2019) - Scime, Natalie V.; Chaput, Katie H.; Faris, Peter D.; Quan, Hude; Tough, Suzanne C.; Metcalfe, Amy
Abstract: Introduction: Pregnancy‐related medical complications are associated with a 2‐ to 5‐fold increased risk of preterm birth (PTB), but the nature of this etiologic relation in context with maternal factors remains poorly understood. Previous studies have generally treated maternal age as a confounder but overlooked its potential as an effect modifier, whereby the magnitude of the effect of complications on PTB could differ significantly across age groups. We investigated whether advanced maternal age (≥35 years) modified the association between pregnancy complications and PTB, and compared population‐attributable fractions of PTB from complications in women older vs younger than 35 years. Material and methods: We analyzed population‐based, cross‐sectional data from the Alberta Discharge Abstract Database for women aged 18‐50 years with singleton live births in hospital between 2014 and 2017 (n = 152 246). Complications were preeclampsia, gestational diabetes, and placental disorders identified using diagnostic codes. Outcomes were spontaneous (sPTB) or iatrogenic (iPTB) PTB before 37 weeks of gestation. We estimated risk ratios and risk differences using modified Poisson and log binomial regression, respectively, adjusting for confounders (pregnancy history, comorbidities). Population‐attributable fractions estimates were calculated from risk ratios. Age modification was tested using interaction terms and Z ‐tests. Results: Prevalence of advanced maternal age was 19.2%. Pregnancy complications and s/iPTB were more common among women aged ≥35 years. Age modified the risk of PTB from preeclampsia only, with risk differences of 9.9% (95% CI 7.2%‐12.6%) in older women vs 6.1% (95% CI 4.8%‐7.4%) in younger women ( P‐ interaction = 0.012) for sPTB, and 29.5% (95% CI 26.0%‐33.1%) vs 20.8% (95% CI 18.9%‐22.6%, P‐ interaction < 0.001) for iPTB. Population‐attributable fractions of s/iPTB types for all complications were consistently 2%‐5% larger in women aged ≥35 years, and significantly larger for preeclampsia (sPTB: 5.1% vs 2.7%, P  = 0.002; iPTB: 18.8% vs 14.0%, P  < 0.001) and placental disorders (sPTB: 12.5% vs 8.7%, P  < 0.001; iPTB: 13.2% vs 8.9%, P  < 0.001). Conclusions: Of the pregnancy complications studied, advanced maternal age only modified the association between PTB and preeclampsia, such that older women with preeclampsia have a higher risk for s/iPTB than younger counterparts. Pregnancy complications contribute to a sizable proportion of PTBs in Alberta, especially among women aged ≥35 years. Findings may inform clinical risk assessment and population‐level policy targeting PTB.